Unraveling the cleft: A historical and comparative review of non-syndromic orofacial cleft etiology and classification - Puškar Nataša; Jakovljević Aleksandar; Simić Radoje; Nikolić Nađa; Miljanović Milica; Arsić Ivan; Petrović Đorđe; Đerlek Amar; Nedeljković Nenad (Balkan Journal of Dental Medicine)
Background/Aim: Orofacial clefts are the most common birth defect of the head. Clefts arise due to a lack of tissue fusion during prenatal development. Various factors can cause the absence of fusion of these structures during 6-8th week of embryonic development. It is proven that the cause of non-syndromic orofacial clefts (NSOFCs) has multifactorial etiology. This review aims to provide a comprehensive summary on etiology and classification of NSOFCs. Material and Methods: Online bibliographic databases were utilized in order to find as many as possible available studies that showed a connection between any environmental factor and genes and NSCL/P, also available studies and books which represented any NSOFC classification system. Results: From the 35 articles and books reviewed, key etiological factors and numerous classification systems that developed over time have been identified. While the multifactorial nature is well-established and proven, specific percentage contributions of individual factors, either environmental or genetic, remain inconclusive. No single classification system is considered perfect, underscoring the need for continued research. Conclusions: Existing classification systems for NSOFCs all have advantages and disadvantages, lacking universal ease of use and comprehensiveness. However, they reflected the evolving understanding of NSOFCs, progressing from anatomical to embryological and developmental perspectives. While several potential etiological factors have been identified, the precise etiology of NSOFCs remain unclear due to complex interplay of factors involved in their occurrence. A definitive cause has not yet been identified.